Patent: An Important Tool for Promoting Drug Discovery and Improving Public Health - Imran, Mohd (Asian Journal of Pharmaceutics (AJP), 2025)
A patent is an important intellectual property concerning pharmaceutical products. This review aims to provide a general overview of patent, patentable pharmaceutical products with examples and patent role in improving public health. The literature for this article was collected from PubMed, Orange Book database of the United States Food and Drug Administration, Espacenet, US Patent and Trademark Office, World Intellectual Property Organization, and other authentic websites. A patent is granted if an invention is novel, non-obvious, and useful. The major patentable pharmaceutical inventions include patent of a compound or drug molecule, the process for preparing a drug, active pharmaceutical ingredient (prodrug, salt, solvate, or specific enantiomer), polymorph (crystalline and amorphous), co-crystals, a second indication of the existing drug, different dosage forms of a drug (solid, semi-solid, liquid, and injectables), drug combinations, particle size based invention, vaccine, diagnostic kit, and medicinal plant-related inventions. Recent drug discovery processes employ artificial intelligence (AI) tools. The AI-based invention is also patentable if it satisfies the patentability criteria. A patent system promotes innovation and economic development and makes its benefits available for public health. In general, a marketed patented pharmaceutical product is expensive. However, the patent system has flexible tools, including research exclusions, compulsory licensing, parallel imports, and monopoly for a limited period to accommodate public interest and health needs. The participation of pharmaceutical researchers (Government sector and private sectors) in developing pharmaceutical innovation is crucial for public health and safety in the long term. Accordingly, a good patent system balances patentee rights and public interest.